PENGARUH DUKUNGAN MERTUA TERHADAP PEMBERIAN ASI EKSKLUSIF PADA BAYI DI PUSKESMAS TANAH LUAS - Aiman, Ummu; Nuraida, Nuraida (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Exclusive breastfeeding is not only based on the condition of the mother, nutrition and birth factors, but there are social factors that are internal and external that must be given to the mother who is breastfeeding, namely family support factors and the surrounding environment. The purpose of this study was to identify the influence of mother-in-law's support for mothers who gave exclusive breastfeeding at Tanah Luas Public Health Center. The urgency in this study is that breast milk is the best nutrition needed by babies. Mothers-in-law are parents of husbands who have different backgrounds, experiences and knowledge from postpartum mothers, based on the phenomenon that occurs not a few mothers-in-law emphasize previous experiences rather than knowledge renewal, because according to researchers there are several experiences of other people. old times are no longer relevant today. Therefore, the researcher wants to know the influence and change the mindset of the mother-in-law on the renewal of health science, especially in breastfeeding. The study used a quantitative design with the Cross Sectional method. This research was conducted in the working area of Tanah Luas Public Health Center with a sample of 60 mothers with the criteria 1) being exclusive breastfeeding, 2) living in 1 house with mother-in-law, 3) willing to be respondents. Based on the explanation above, it can be concluded that the category of mothers-in-law who support the process of exclusive breastfeeding is 52.7% while mothers who do not give exclusive breastfeeding are 47.3%. After the Chi-Squer test was carried out, the P value was 0.01, which means that the hypothesis is accepted that there is a strong influence between providing parent-in-law support to the process of exclusive breastfeeding to infants at the Tanah Luas Public Health Center. Â  Â 